RESEARCH ON BOLT CONNECTION LOOSE MECHANISM UNDER DYNAMIC TENSION COMPRESSION AND SHEAR LOAD - FANG ZiFan; WU Hang; CAO Gang; HE KongDe; GE XuFu; XIE XuGuang (Jixie qiangdu)
Aiming at the loosening of bolt connection in the rotating mechanism under dynamic tension compression and shear load,the failure mechanism and its influencing factors are studied by using virtual prototyping technology and finite element analysis method. First,based on the virtual prototype technology,the load of failure bolt connection structure is extracted;Secondly,the finite element method is used to analyze the influence factors of bolt number,preload,thickness of the connecting piece and spring gasket. The evaluation index system of digital analysis is set up to guide the design of the measures for improving the anti loosening. In this paper,the design and research on the bolt of a servo device rotating mechanism is taken as an example. The method of digital design and analysis is carried out,which solves the problem of bolt connection loose. The conclusion shows that the improved design is consistent with the practical engineering,and bolt connection structure is free from loosening and failure.